Short run and long run in trade models: A note - Mauro Rodrigues (EconomiA, 2013)
This paper aims to capture key features of the Ricardo–Viner (RV) and Heckscher–Ohlin (HO) theories in a single dynamic general equilibrium framework. We use a simple 2-sector 2-factor model with adjustment costs associated with the movement of capital across sectors. We analyze the economy's response to exogenous changes in factor endowments and output prices. Our model reproduces the predictions of the RV theory in the short run (moment immediately after a parameter change) and the predictions of the HO model in the long run (steady state implied by a new set of parameters). Numerical examples of transition paths are also provided. – – Este artigo busca capturar as principais características dos modelos de Ricardo–Viner (RV) e de Heckscher–Ohlin (HO) em um único ambiente. Utilizamos um simples modelo de dois fatores e dois setores, com custos de ajustamento associados ao movimento de capital entre indústrias. Analizamos ent\~ao a resposta desta economia a mudanças exógenas nas dotaç\~oes de fatores e nos preços dos produtos. Nosso ambiente reproduz os resultados do modelo de RV no curto prazo (momento imediatamente posterior à mudança nos parâmetros) e do modelo de HO no longo prazo (estado estacionário correspondente ao novo conjunto de parâmetros). Exemplos numéricos de transiç\~oes s\~ao também apresentados.
Keywords: F11; F16; 330; Trade; Factor mobility; Dynamics